Screening of Verticillium lecanii isolates for controlling of Cinara atlantica - Leite, Maria Silvia Pereira; Penteado, Susete do Rocio Chiarello; Zaleski, Scheila Ribeiro Messa; Camargo, Joelma Melissa Malherbe; Ribeiro, Rodrigo Daniel (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The aim of this study was to evaluate the pathogenicity of Verticillium lecanii isolates against Cinara atlantica, and the LC50 of the best strain. For selection tests, nymphs of C. atlantica were placed on individual pine seedling with 20 isolates and one control, in a total of 21 treatments and ten replicates. For the LC50 estimation it was used the CG 904 strain with six concentrations and ten replicates. VL 6, CG 902 and VL 2 produced the highest mortality, of 72.22%, 67.34% and 67.31%, respectively. The control plot showed mortality of 15.6%. The LC50 of the CG 904 strain indicated mortality of 100% at the concentration of 108 conidia mL-1; LC50, 2x105 conidia mL-1; and LT50, 4.4 days.